2021
DOI: 10.2174/1573397116666201216164013
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Approach Towards Rheumatoid Arthritis Treatment

Abstract: : Rheumatoid arthritis is an auto-immune disorder, recognized by cartilage as well as bone destruction which causes irreversible joint deformities, which further results in functional limitations in the patient. Genes like HLA-DRB1 and PTPN22 are likely implicated in the genetic predisposition of rheumatoid arthritis pathology. The first and foremost clinical manifestation person with rheumatoid arthritis, is joint destruction followed by cartilage and bone destruction caused by cell-cell interactions. The cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 120 publications
1
2
0
Order By: Relevance
“…The CIA mouse model is commonly used to study RA [ 32 ]. Consistent with previous reports [ 33 ], our data showed that DI could effectively attenuate CIA, as demonstrated by the alleviation of RA-related symptoms, including synovial hyperplasia, inflammatory cell infiltration, bone destruction, and cartilage erosion, combined with a reduction in arthritis score, paw thickening and recovered joint bone structure. Abnormal T cell activation and the subsequent persistent inflammatory response play a crucial role in RA development [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…The CIA mouse model is commonly used to study RA [ 32 ]. Consistent with previous reports [ 33 ], our data showed that DI could effectively attenuate CIA, as demonstrated by the alleviation of RA-related symptoms, including synovial hyperplasia, inflammatory cell infiltration, bone destruction, and cartilage erosion, combined with a reduction in arthritis score, paw thickening and recovered joint bone structure. Abnormal T cell activation and the subsequent persistent inflammatory response play a crucial role in RA development [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…The interaction between DCs and CD4 + T cells was shown by an increase in a series of key biomarkers, such as RANKL, IL-12, IFN-γ, and TGF-β [ 50 ], which promoted the development and progression of RA. igDC stimulation activated CD4 + T-cell homeostasis by facilitating the release of inflammatory cytokines from functional T cells [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…bDMARDs include mainly tumor necrosis factor-α (TNF-α) inhibitors, interleukin-6 (IL-6) antagonists, and costimulatory factor modulators. bDMARDs are characterized by special targeting factors, but the costs are higher than those of other treatment methods, and the economic burden of patients is greater [ 21 ].…”
Section: Introductionmentioning
confidence: 99%